Aqueous Self-Assembly of Peptide–Diketopyrrolopyrrole Conjugates with Variation of N-Alkyl Side Chain and π-Core Lengths - Panda, Sayak Subhra; Tovar, John D. (Organic Materials, 2021)
Peptidic sequences when conjugated to π-electronic groups form self-assembled networks of π-electron pathways. These materials hold promise for bio-interfacing charge transporting applications because of their aqueous processability and compatibility. In this work, we incorporated diketopyrrolopyrrole (DPP), a well-established π-core for organic electronic applications, within the peptidic sequence. We embedded different numbers of thiophene rings (2 and 3) on both sides of the DPP to alter the length of the π-cores. We also varied the length of the N-alkyl side chains (methyl, butyl, hexyl) attached to the DPP core. These variations allowed us to explicitly study the effect of π-core and N-alkyl side-chain length on photophysical properties and morphology of the resulting nanomaterials. All of these molecules formed H-type aggregates in the assembled state. Longer π-cores have relatively red-shifted absorption maxima, whereas the N-alkyl variation did not present significant photophysical changes.
Keywords: peptide-π conjugates; diketopyrrolopyrroles; aqueous self-assembly; side-chain engineering